Cardiac Surveillance for Early Detection of Late Subclinical Cardiac Dysfunction in Childhood Cancer Survivors After Anthracycline Therapy - Sofia, Rosaria; Melita, Veronica; De Vita, Antonio; Ruggiero, Antonio; Romano, Alberto; Attinà, Giorgio; Birritella, Lisa; Lamendola, Priscilla; Lombardo, Antonella; Lanza, Gaetano Antonio; Delogu, Angelica Bibiana (Frontiers in Oncology, 2021)
Background: In childhood cancer survivors (CCSs) anthracycline-related cardiotoxicity is an important cause of morbidity and late mortality, but the optimal modality of cardiac surveillance still remains to be defined. Aim of this study was to assess which non-invasive echocardiography-based functional cardiac measures can detect early subclinical myocardial changes in long-term pediatric cancer survivors who had received anthracycline therapy. Methods: Twenty anthracycline-treated long-term CCSs and 20 age, sex and body surface area matched healthy controls were enrolled in this study. Among cancer survivors, the mean age at diagnosis was 6.5±4.4 years; mean follow-up time after the completion of therapy was 6.5±2.8 years; the mean cumulative anthracycline dose was 234.5±87.4 mg/m2. All subjects underwent a comprehensive functional echocardiographic protocol study including two-dimensional echocardiography (2D Echo), tissue Doppler imaging (TDI), speckle tracking (STE) and three-dimensional echocardiography (3D Echo). Results: No significant differences in two-dimensional LV ejection fraction, diastolic parameters and STE-derived myocardial strain were observed between patients treated with anthracyclines and healthy controls. Myocardial Performance Index was significantly prolonged (p=0.005) and three-dimensional LV ejection fraction was significantly reduced (p=0.002) in CCSs than in controls, even though most values were within the normal range. There were no significant correlations between 2D, STE and 3D echocardiographic parameters and age at diagnosis or duration of follow-up. No significant differences were found by stratifying cancer patients according to established risk factors for anthracycline cardiomyopathy. Conclusions: This study found significantly reduced three-dimensional ejection fraction in CCSs compared with controls, despite no significant differences in two-dimensional ejection fraction and longitudinal strain values. These findings suggest that long-term pediatric cancer survivors who had received anthracycline therapy may be found to have subclinical features of myocardial dysfunction. However further studies are needed to demonstrate the validity of new imaging techniques, including STE and 3D Echo, to identify patients at risk for cardiomyopathy in the long-term follow-up of CCSs.